KARAKTERISTIK KEPEMIMPINAN TRANSFORMASIONAL DAN KARAKTERISTIK WIRAUSAHA PADA USAHA KECIL MENENGAH (UKM) KOTA MAGELANG - Murni, Rochiyati (Jurnal Analisis Bisnis Ekonomi, 2010)
This research is condusted in Small Medium Enterpresises (SMEâs) in Magelang, aim to know the the relationship betwee the characteristic of transformasional leader and the implementaion of chacarteristicâs entrepreneur. Researchis conducted at July 2010. Reasearch variable consisted of the variable chacarteristic of the transformational leader. They are charisma, inspirational, intellectual stimulation and individual consideration. Variable of characteristicâs entrepreneur are the high commitment, leadership, ability catch the opportunity, dare to risk, creative, self-supporting, adaptive capability and motivate achievement. The sampling method is purposive sampling, with the amount sample is 35 SMEâs in Magelang. The analyze data are correlation and analyze of variance. Result of calculation show that there is positive and significant relation between the characteristic of transfrmational leaders and the implementation of chacarteristicâs entrepreneur in SMEâs in Magelang.